A mobile, in-situ soil bin test facility to investigate the performance of maresha plough - Gebregziabher, Solomon; De Swert, Karel; Saeys, Wouter; Ramon, Herman; De Ketelaere, Bart; Mouazen, Abdul Mounem; Gebrehiwot, Kindeya; Deckers, Jozef; De Baerdemaeker, Josse (Elsevier, 2016)
Ethiopia is well known for its use of an ard plough dating from antiquity – maresha – which fractures and disturbs the soil. However, hardly any notable progress of experimental research on this animal drawn tillage tool in the field has been made. The attendant problems in current practise are soil-maresha interaction, viz., uneven oxen strength along with different pace of walking, uncontrolled implement behaviour, and field conditions. Taking stock of the experimental research on animal drawn tillage tools in general, most of the documented works on the dynamics of the interaction between soil and animal drawn tillage tools tend to rely on trial-and-error based on factors mainly based on experience and cultural context. As such, no research tailored to systematically handle the link between maresha plough and soil bin experiments exists. To this aim, this study developed a mobile in-situ soil bin facility in which the system was calibrated, tested, and evaluated under outdoor experimental conditions, wherein online measurements of draught, speed, and depth of tillage were carried out. The insights and observations gained from the experimentation were discussed and reported in terms of smooth run, overload, cyclic forces, zero speed with minimal force, stoppage, speed measurement with no force, force measurement with no speed, and low speed with low force.
Keywords: Draught; In-situ; Maresha; Overload; Tillage depth; Tillage speed